2015
DOI: 10.1111/ina.12221
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to organophosphate and polybrominated diphenyl ether flame retardants via indoor dust and childhood asthma

Abstract: Although the ubiquitous detection of polybrominated diphenyl ether (PBDE) and organophosphate flame retardants (PFRs) in indoor dust has raised health concerns, only very few epidemiological studies have assessed their impact on human health. Inhalation of dust is one of the exposure routes of FRs, especially in children and can be hazardous for the respiratory health. Moreover, PFRs are structurally similar to organophosphate pesticides, which have been associated with allergic asthma. Thus, we investigated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 44 publications
(64 reference statements)
1
21
1
Order By: Relevance
“…At the same time, we noted a weak negative correlation between the levels of BDE‐99 and TV and TT. A weak negative correlation was also detected between the levels of BDE‐209 and E. It may be assumed that the negative value of the Spearman's rank correlation coefficient ( r s ) may have resulted from electronic equipment which did not contain PBDEs and could not be the source of origin of these dust compounds, while other elements of home furnishings and fittings may be such a source (Canbaz et al., ; Rauert et al., ; de Wit et al., ). Cunha et al.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, we noted a weak negative correlation between the levels of BDE‐99 and TV and TT. A weak negative correlation was also detected between the levels of BDE‐209 and E. It may be assumed that the negative value of the Spearman's rank correlation coefficient ( r s ) may have resulted from electronic equipment which did not contain PBDEs and could not be the source of origin of these dust compounds, while other elements of home furnishings and fittings may be such a source (Canbaz et al., ; Rauert et al., ; de Wit et al., ). Cunha et al.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have identified associations between asthma and exposure to biological particle‐bound contaminants such as gram‐positive and gram‐negative bacteria, endotoxins, and several airborne fungi . Exposure to particle‐bound semi‐volatile organic compounds (SVOCs) is also implicated in the development and exacerbation of asthma and allergies . Phthalate exposure is associated with the prevalence of children's asthma; however, organophosphate ester (OPE) exposure and its association with asthma are less clear …”
Section: Introductionmentioning
confidence: 99%
“…Exposure to particle‐bound semi‐volatile organic compounds (SVOCs) is also implicated in the development and exacerbation of asthma and allergies . Phthalate exposure is associated with the prevalence of children's asthma; however, organophosphate ester (OPE) exposure and its association with asthma are less clear …”
Section: Introductionmentioning
confidence: 99%
“…Exposure to PBDEs occurs in the indoor environment through several routes including ingestion, inhalation, and dermal contact. Much attention has been paid to indoor dust, which is a major sink for PBDEs and an important pathway for human exposure to PBDEs (Chao et al, 2014c;Canbaz et al, 2015;Newton et al, 2015). Furthermore, several reports indicate that most PBDEs exposures are from indoor dust and not food (Lorber, 2008;Johnson-Restrepo and Kannan, 2009;Kang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several reports indicate that most PBDEs exposures are from indoor dust and not food (Lorber, 2008;Johnson-Restrepo and Kannan, 2009;Kang et al, 2011). A recent study failed to find a significant relationship between PBDEs in mattress dust (indoor dust) and development of childhood asthma (Canbaz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%